2015
DOI: 10.1638/2014-0141r.1
|View full text |Cite
|
Sign up to set email alerts
|

DIAGNOSIS AND PALLIATIVE MANAGEMENT OF ATOPIC DERMATITIS IN A MALAYAN FLYING FOX (PTEROPUS VAMPYRUS)

Abstract: A 7-yr-old male Malayan flying fox (Pteropus vampyrus) presented with chronic, recurrent bilateral conjunctivitis and palpebral chemosis. Variable, temporary response to topical ocular antibiotic-corticosteroid therapy occurred. Histopathology of a conjunctival biopsy was consistent with allergic conjunctivitis. The bat was treated systemically with antihistamines and topically with an ocular antibiotic-corticosteroid combination for acute episodes of conjunctivitis. Pruritus, severe alopecia of the head and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, it is unclear why rehabilitators reported pruritus whereas zoos did so infrequently, and why zoos reported blisters on wing membranes whereas rehabilitators did not. Pruritus has been reported previously in a single case of presumptive atopic dermatitis in a captive Malayan flying fox ( Pteropus vampyrus ) . Alopecia has been reported previously in both captive and free‐ranging bats .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, it is unclear why rehabilitators reported pruritus whereas zoos did so infrequently, and why zoos reported blisters on wing membranes whereas rehabilitators did not. Pruritus has been reported previously in a single case of presumptive atopic dermatitis in a captive Malayan flying fox ( Pteropus vampyrus ) . Alopecia has been reported previously in both captive and free‐ranging bats .…”
Section: Discussionmentioning
confidence: 86%
“…Apart from white nose syndrome (WNS), a fungal disease affecting the skin and wing membranes of hibernating bats, which has led to over a million fatalities since it was first recognized in 2006, little has been reported on bat skin disease. Individual cases of skin disease are described in captive bats held in zoos and for rehabilitation including reports of alopecia, atopic dermatitis, vitiligo and fungal dermatitis . Necrotic disease of the pinna was reported in a translocation project in New Zealand short‐tailed bats ( Mystacina tuberculata ) .…”
Section: Introductionmentioning
confidence: 99%
“…As in all vertebrates, viral infections were found to trigger a humoral immunity, although titers varied depending on the virus, as described above. As described for other bat species [63][64][65][66][67], four immunoglobulin isotypes Aside from the innate immune response, intriguing features of Jamaican fruit bat adaptive immunity could be identified. As in all vertebrates, viral infections were found to trigger a humoral immunity, although titers varied depending on the virus, as described above.…”
Section: Discussionmentioning
confidence: 89%
“…As in all vertebrates, viral infections were found to trigger a humoral immunity, although titers varied depending on the virus, as described above. As described for other bat species [63][64][65][66][67], four immunoglobulin isotypes (IgM, IgE, IgA, and IgG) were expressed in the Jamaican fruit bat (Table 1) [21]. Interestingly, IgD appears to be specific for insectivorous bat species, and is thus not encoded in Jamaican fruit bats, as well as other frugivorous species genomes, such as the New World Seba's shorttailed bat [58,65], the South Asian greater short-nosed fruit bat (Cynopterus sphinx) [65], the black flying fox, and the large flying fox [45,63].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to WNS, skin diseases were not commonly reported in bats, although dermatophytes are known to grow on bat skin ( Simpson et al , 2013 ; Lorch et al. , 2015 ; McAlpine et al , 2016 ) and dermatitis has been documented ( Goodnight, 2015 ; Fountain et al , 2017 , 2019 ). A global survey of captive bats found that some species are more frequently reported with skin diseases compared to others, and some skin lesions show seasonal patterns with increased frequency in the winter for bats exposed to outdoor temperatures ( Fountain et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%